A study of the dissolution of atmospherically derived trace metals into North Atlantic seawater ... - Fishwick, Matthew Paul (Plymouth University, 2016)
Chapter 3 has been used to create a manuscript, which was published in Global Biogeochemical Cycles in 2014, see reference: Fishwick, M. P., P. N. Sedwick, M. C. Lohan, P. J. Worsfold, K. N. Buck, T. M. Church, and S. J. Ussher (2014), The impact of changing surface ocean conditions on the dissolution of aerosol iron, Global Biogeochemical Cycles, 28, doi:10.1002/2014GB004921. Chapters 4 and 5 are currently being used to create manuscripts for publication. ... : The aim of this study was to investigate the factors that affect the dissolution of a suite of trace metals from aerosols into seawater from wet and dry deposition, with a focus on important trace metals: manganese (Mn), iron (Fe), cobalt (Co), nickel (Ni), copper (Cu) and lead (Pb). To this end, aerosol and rainwater samples were collected from Tudor Hill (Bermuda) and Penlee Point (Cornwall) atmospheric observatories and surface seawater samples were collected from the Sargasso Sea and the Celtic Sea. These representative aerosol, rainwater and seawater samples were used in aerosol leaching and rainwater mixing experiments, which simulated the processes of mixing and trace metal dissolution following wet and dry deposition as closely as possible within the laboratory. Key variables were changed to investigate the effect of aerosol source/composition, seawater temperature, pH, dissolved oxygen concentration and organic ligand amendments on aerosol and rainwater trace metal dissolution. Results for aerosol ...